Analisis pemetaan media tentang transaksi pembiayaan akad sharf di Indonesia dengan NVivo: Studi literatur review - Rohmadi; Doni Yusuf Bagaskara (Journal of Accounting and Digital Finance, 2024)
This research aims to determine the media mapping analysis of Sharf Contract Financing Transactions in Indonesia using the NVivo tool. This research uses qualitative methodology with the help of NVivo and a literature review. "Data analysis techniques include: (1) mapping the number of news article codes based on qualitative analysis such as meaning, mechanisms, and laws, around "Sharf" using NVivo 14 software; (2) mapping the visualization results with a hierarchical diagram and test the correlation between media articles using qualitative analysis; (3) mapping research topics with Worldcloud or a collection of words that are often discussed in media articles; and (4) Testing the significance value between media articles to determine the size of the correlation around the topic "Sharf." This research shows that the topics often discussed in media articles about Sharf are understanding and law. Meanwhile, topics that are rarely discussed by media articles about Sharf are mechanisms and law. The implications of this research show that analysis using NVivo and Literature Review tools can be a recommendation for increasing public literacy regarding rahn financing through media articles.